THE RELATIONSHIP BETWEEN KNOWLEDGE TOWARDS DENGUE PREVENTION BEHAVIOR IN THE COMMUNITY IN MEDAN DENAI SUB-DISTRICT - Haura Taqiya Ramadina Siregar; Hendri Wijaya; Andika Pradana; Sri Melinda Kaban (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Dengue remains a major public health problem in tropical countries, including Indonesia. The increasing incidence of dengue requires active community participation in prevention efforts. Knowledge is an important factor influencing dengue prevention behavior. This study aimed to analyze the relationship between knowledge level and dengue prevention behavior among the community in Medan Denai Sub-district, Medan. This study employed an analytical observational design with a cross-sectional approach and was conducted in August 2024. A total of 131 respondents were selected using consecutive sampling. Data were collected through face-to-face interviews using a structured questionnaire and analyzed using the chi-square test. The results showed that most respondents had a very good level of knowledge (59.5%), while dengue prevention behavior was predominantly in the sufficient category (42.7%). Bivariate analysis revealed a statistically significant relationship between knowledge level and dengue prevention behavior (p = 0.007). These findings indicate that higher knowledge levels are associated with better dengue prevention behavior. Strengthening community-based health education and cross-sector collaboration at the primary healthcare level is essential to promote sustainable dengue prevention practices.